Análise técnica da utilização de luminárias com tecnologia led em sistemas de iluminação de aeroportos - MAGALHÃES, Lúcio Antônio Pereira (2015)
Airports are used with some frequency by most people, whether for leisure, business, personal reasons, etc; which shows its importance to society. The airport lighting systems are very important to its operation and visual comfort of the people. This work has as main objective technical analysis of the use of lamps with LED technology at airports lighting systems to replace conventional types of commonly used lamps. The specific objective of this study is to analyze the existing lighting systems at airports, especially large Brazilian airports, related to group 1, category I, covering several lighting systems. Passenger terminal lighting systems (lobby, office areas, shops and banks) and the parking lots using commercial fixtures; lighting systems of cargo terminals, which use industrial fixtures; the lighting systems of access routes to the airport, using public fixtures; The bright aid to flight systems on runways and taxyways using specific fixtures for airports as the marking fixtures, the lighting systems of the aircraft apron, using projectors with metal halide lamps. In this work, five case studies were studied in the Salvador airport: Hall 1st floor of the passenger terminal; storage area of the cargo terminal, access roads near the cargo terminal, apron 3 (aircraft parking apron), taxiway lighting; analyzes the types of used light fixtures and lamps and makes a comparative study of the replacement of these luminaires with conventional light bulbs with lamps with LED technology, from the perspective of sustainability, economics obtained by analyzing procurement costs, power consumption, maintenance, energy efficiency and environment preservation, either in use or disposal of luminaires and lamps. To achieve the goals in the five case studies gathering data on the Salvador airport and also through research scientific works, articles, monographs and dissertations or technical work done by professionals working in the airports managed by INFRAERO, technical material (specifications , memorials) civil aviation authoritin related to civil aviation: ANAC, Infraero, aeronautical, etc; information and technical catalogs of luminaire manufacturers, lamps and equipment related to air navigation. The conclusions of the work show that the use of luminaires with LED technology at airports lighting systems is an alternative more efficient, sustainable and brings economic advantages over the use of luminaires with conventional lamps.